Remote tactical training of national teams - Kuliev, R. (International Journal of Computer Science in Sport, 2002)
Nowadays National teams usually suffer from the lack of time for joint training sessions. As a result National teams are less coordinated than club teams. Remote teaching is now widely in use in education. Such a method could decide and provide a solution to most problems concerning tactical team training before real training sessions.